STRATEGI PROMOSI PRODUK MELALUI DIGITAL MARKETING BAGI UMKM TERDAMPAK PANDEMI COVID'19 BERDASARKAN KEPUTUSAN KONSUMEN - Tabroni Tabroni; Mamay Komarudin (Jurnal Riset Entrepreneurship, 2021)
In this situation, especially during the covid'19 pandemic, many companies inevitably have to make an overhaul of the management within the company itself as well as in the overhaul of product promotion strategies used by companies that are considered less effective to use during the increasingly severe covid'19 pandemic. This research is a research entitled Product Promotion Strategy Through Digital Marketing for MSMEs Affected by the Covid'19 Pandemic. The purpose of this research is to give an overview of the form of promotion carried out by companies during the covid'19 pandemic that cannot be predicted to end the covid'19 pandemic. This research is descriptive qualitative research that is using literature or focused literature studies to explain the results of research obtained by researchers. The result of this research is to provide an overview of the relationship of promotion through digital marketing with consumer decisions during the covid'19 pandemic.